Analysis of the Impact of Self-Efficacy on Student Learning Outcomes in Electromagnetic Induction Material - Bernathasari, Tesalonika; Hutauruk, Novri Elisabeth; Miyaqi, Iqlides Ahmad; A’yun, Dian Rifatul; Ariswan, Ariswan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study aims to analyze the impact of self-efficacy on student learning outcomes on electromagnetic induction material. This research takes the type of descriptive quantitative research, a method that focuses on analyzing numerical data using statistical methods. It was conducted at MA Ali Maksum Yogyakarta with the research subjects of XII MIPA class students totaling 30 respondents. Data collection techniques using cognitive tests and self-efficacy questionnaires assisted by Google Form applications. The results showed that the hypothesis can be accepted, namely there is a correlation between the level of self-efficacy and the results of student learning tests even though the correlation found has a weak category because it only has a share of 8.1%. This shows that the domain of student confidence, especially in terms of solving problems is still at a low level so that there is a tendency for students to solve problems based on memorizing equations. The existence of limitations in conducting research limits it in uncovering other aspects outside of self-efficacy in obtaining learning outcomes. Through the information obtained that self-efficacy on learning outcomes, teachers can apply a varied atmosphere, model, and learning process to optimize student potential which will have an impact on student learning outcomes.